Analisis Sistem Kompensasi, Kompetensi Emosi, dan Kinerja Penyelesaian Sengketa Pemilu: An Analysis of Compensation Systems, Emotional Competence, and Performance in Electoral Dispute Resolution - Thayib, Thayib (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2005)
The proper functioning of election dispute resolution mechanisms is critical for democratic consolidation, yet Panwaslu performance is hindered by inadequate compensation and variable emotional competence among members. Grounded in organisational behaviour and human resource management theories, the study examines compensation systems and emotional competence as determinants of performance. It analyses the influence of these factors on Panwaslu members’ performance in resolving electoral disputes, both jointly and separately. A quantitative approach using multiple regression analysis was employed, involving 129 respondents from district and city Panwaslu across East Java during the 2004 legislative and presidential elections. Data were collected through questionnaires, observation, documentation, and interviews. The findings show that the compensation system alone does not significantly affect dispute resolution performance (t=1.014, p=0.313), whereas emotional competence has a significant positive influence (t=2.507, p=0.013). Together, the variables explain 16.5% of the variance in performance (R²=0.165, F=0.000). The study concludes that emotional competence is the dominant factor and recommends that future Panwaslu recruitment prioritise indicators of emotional competence and that performance-based compensation be more explicitly formulated to enhance dispute resolution effectiveness. Mekanisme penyelesaian sengketa Pemilu yang berfungsi baik sangat krusial bagi konsolidasi demokrasi, namun kinerja Panwaslu menghadapi tantangan dari sistem kompensasi yang belum memadai dan kompetensi emosi anggota yang bervariasi. Penelitian ini berlandaskan pada teori perilaku organisasi dan manajemen sumber daya manusia, khususnya sistem kompensasi dan kompetensi emosi sebagai determinan kinerja. Tujuan penelitian adalah menganalisis pengaruh sistem kompensasi dan kompetensi emosi terhadap kinerja anggota Panwaslu dalam menyelesaikan sengketa Pemilu, baik secara simultan maupun parsial. Metode yang digunakan adalah pendekatan kuantitatif dengan analisis regresi berganda terhadap 129 responden dari Panwaslu Kabupaten/Kota di Jawa Timur pada Pemilu legislatif dan presiden 2004. Pengumpulan data dilakukan melalui kuesioner, observasi, dokumentasi, dan wawancara. Hasil penelitian menunjukkan bahwa sistem kompensasi secara parsial tidak berpengaruh signifikan terhadap kinerja penyelesaian sengketa (t=1,014; p=0,313), sedangkan kompetensi emosi berpengaruh positif signifikan (t=2,507; p=0,013). Secara simultan, kedua variabel menjelaskan 16,5% varians kinerja (R²=0,165; F=0,000). Kesimpulannya, kompetensi emosi merupakan faktor dominan. Penelitian merekomendasikan agar rekrutmen Panwaslu ke depan memperhatikan aspek kompetensi emosi dan perumusan kompensasi berbasis kinerja secara lebih rinci.